Alternative Combined Retrograde–Antegrade Use of a Re-entry Device in the Revascularization of a Surgically Ligated Superficial Femoral Artery Occlusion - Gandini, Roberto; Raso, Armando; Di Martino, Arezia; Salimei, Fabio; Morosetti, Daniele (Journal of Clinical Interventional Radiology ISVIR, 2021)
We report a case of a diabetic patient with critical limb ischemia, who previously underwent thromboendarterectomy at the right lower extremity, resulting in surgical ligation at the proximal third of the right superficial femoral artery (SFA). Twenty months later, the patient developed foot ulcers; endovascular treatment was therefore performed. After obtaining a retrograde right SFA subintimal access, directly puncturing the occluded segment of the artery, a re-entry intravascular ultrasound-guided catheter was used to gain proximal re-entry. Then, the same device was used again, in antegrade fashion, to obtain re-entry into the patent popliteal artery. A covered stent was deployed in the site of the surgical closure. In the following 3 months, foot ulcers healed.
Keywords: surgical ligationrevascularization; re-entry